2016
DOI: 10.1016/j.molcel.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Imaging Reveals that Rad4 Employs a Dynamic DNA Damage Recognition Process

Abstract: SUMMARY Nucleotide excision repair (NER) is an evolutionarily conserved mechanism that processes helix-destabilizing and/or -distorting DNA lesions, such as UV-induced photoproducts. Here, we investigate the dynamic protein-DNA interactions during the damage recognition step using single-molecule fluorescence microscopy. Quantum dot-labeled Rad4-Rad23 (yeast XPC-RAD23B ortholog) forms nonmotile complexes or conducts a one-dimensional search via either random diffusion or constrained motion. Atomic force microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 53 publications
(93 reference statements)
6
104
0
Order By: Relevance
“…1 Single molecule studies have been employed to study the dynamics of various NER factors including XPC, XPD, and RPA. 2629 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Single molecule studies have been employed to study the dynamics of various NER factors including XPC, XPD, and RPA. 2629 …”
Section: Introductionmentioning
confidence: 99%
“…40 Single-molecule fluorescence microscopy studies have provided further support for the “twist-open” and the “kinetic gating” lesion recognition mechanisms. 29 …”
Section: Introductionmentioning
confidence: 99%
“…In a recently published study, we characterized the diffusive behavior of quantum dot-labeled Rad4-Rad23 (the yeast homolog of human XPC-HR23B, Figure 2A), the damage sensor in yeast nucleotide excision repair (NER), using the single-molecule DNA tightrope assay (Kong et al, 2016). It was shown that Rad4-Rad23 utilizes the facilitated diffusion mechanism (See Section 4 for in-depth discussion on the topic) to search for lesions in DNA.…”
Section: Diffusion Of a Dna Repair Proteinmentioning
confidence: 99%
“…His-tagged Rad4-Rad23 (yellow, pink, cyan, and blue) is labeled with streptavidin (red)-coated quantum dot (green) through a His antibody (His-Ab)-biotin conjugate (gray). Adapted from Kong et al , (2016) Mol Cell , 64 , 376 – 387 with permission.…”
Section: Figurementioning
confidence: 99%
“…A recent report 9 revealed that the yeast protein Rad4, which is involved in nucleotide-excision repair, does not directly bind damaged sites, but instead diffuses for up to 1 kilobase around the damage, providing a dynamic platform for the recruitment of other repair proteins. Furthermore, the protein Mfd, which dislodges RNA polymerase enzymes that become stalled while transcribing DNA, then scouts ahead for DNA damage on the transcribed strand 10 .…”
mentioning
confidence: 99%